2019
DOI: 10.1103/physrevd.99.016017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic modes in a magnetized chiral plasma with vorticity

Abstract: By making use of a covariant formulation of the chiral kinetic theory in the relaxation-time approximation, we derive the first-order dissipative hydrodynamics equations for a charged chiral plasma with background electromagnetic fields. We identify the global equilibrium state for a rotating chiral plasma confined to a cylindrical region with realistic boundary conditions. Then, by using linearized hydrodynamic equations, supplemented by the Maxwell equations, we study hydrodynamic modes of magnetized rotatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…This type of collision integral was recently used in Refs. [60][61][62]. The above collision integral has to be taken with care as it assumes that impurity scattering relaxes both regular and axial charge densities [63].…”
Section: Collisions With Single Effective Relaxation Timementioning
confidence: 99%
“…This type of collision integral was recently used in Refs. [60][61][62]. The above collision integral has to be taken with care as it assumes that impurity scattering relaxes both regular and axial charge densities [63].…”
Section: Collisions With Single Effective Relaxation Timementioning
confidence: 99%
“…In contrast to the original predictions, however, recently we found that the CMW should be a diffusive mode in the weakly coupled plasma in the long-wavelength limit [30]. The novel aspect of our analysis was the rigorous treatment of dynamical electromagnetism in chiral plasmas.…”
Section: Introductionmentioning
confidence: 75%
“…In order to give a self-contained presentation, let us start by briefly reviewing the key details of the CMW dynamics for a chiral plasma obtained in Ref. [30]. Since the local vorticity plays no vital role in the propagation of the CMW, we will consider only the case of a non-rotating plasma.…”
Section: Hydrodynamic Analysis Of Collective Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…See[54] for a related work 13. For a general system with U (1) triangle anomalies some expressions have been found for these coefficients in[20].…”
mentioning
confidence: 99%